THE RELATIONSHIP OF TEENAGER KNOWLEDGE LEVEL ABOUT HIV/AIDS WITH HIV/AIDS PREVENTION BEHAVIOR DURING THE COVID-19 PANDEMIC AT SMA KARTINI, BATAM CITY - Indah Mastikana; Erika Fariningsih; Risma Ikha Paramitha (Bajang Institute, 2022)
HIV continues to be a major global public health problem. A person infected with HIV will experience a gradual decline in immunity and will develop AIDS. The highest rates of HIV-infected cases were reported in the age groups of 25-49 years and 20-24 years. However, there is a surprising fact about the 15-19 year old group which is a group of teenagers. The risk of HIV infection in teenagers is caused by several factors. One of these factors is the level of knowledge. Teenager knowledge about free sex and HIV/AIDS transmission is still low. Based on data obtained from the P2P Division report of the Batam City Health Office, HIV cases has decreased compared to 2020 as many as 541 cases to 484 cases in 2021 with the largest distribution of cases in the Lubuk Baja District area with 245 HIV sufferers. The Covid-19 pandemic has hampered efforts to control disease, including controlling HIV/AIDS, especially in Batam City, including educational activities related to HIV/AIDS, which have stalled due to restrictions on mobility. The purpose of this study was to determine the relationship between the level of knowledge of teenagers about HIV/AIDS with HIV/AIDS preventive behavior during the Covid-19 pandemic at SMAS Kartini, Batam City. This type of correlation research with cross sectional approach. Data were obtained from distributing questionnaires to students of SMA Kartini City, Batam aged 15-18 years, totaling 74 samples. The results showed that 36 respondents with good knowledge had good behavior in preventing HIV/AIDS transmission, 35 respondents (97.2%) and 1 respondent (2.8%). There are 29 respondents with sufficient knowledge, namely 28 respondents (96.5%) who behave well in preventing HIV/AIDS transmission and 1 respondent (3.5%). Lack of knowledge of 9 respondents, namely those who behave well in preventing the transmission of HIV/AIDS. There is no significant relationship between the level of knowledge and prevention behavior (p=1,000). In conclusion, there is no relationship between the level of knowledge of teenagers about HIV/AIDS with HIV/AIDS prevention behavior during the COVID-19 pandemic at SMAS Kartini, Batam City, in the 2021-2022 academic year.